Effects of dipeptidyl peptidase‐4 inhibitors on transforming growth factor‐β1 signal transduction pathways in the ovarian fibrosis of polycystic ovary syndrome rats - Wang, Fang (J Obstet Gynaecol Res, 2018)
AIM: Examine the effects of dipeptidyl peptidase‐4 (DPP4) inhibitor Sitagliptin on the transforming growth factor‐β1 (TGF‐β1) signal transduction pathway in polycystic ovary syndrome (PCOS) rats with ovarian fibrosis. METHODS: Thirty rats were divided randomly into the PCOS model group, Sitagliptin treatment group and blank control group. Dehydroepiandrosterone was administered to the model group and treatment group to establish the models. Then, the phenotype of rats was recorded, and the serum sex hormone levels were measured. The pathological structures of the rat ovaries were observed. The protein and mRNA expression levels of DPP4, connective tissue growth factor (CTGF), TGF‐β1 and Smad2/3 in the ovaries were analyzed. RESULTS: There was no statistically difference in fasting body weight and blood glucose among the three groups before Sitagliptin treatment (P > 0.05). The fasting blood glucose level was significantly decreased after the administration of Sitagliptin (P < 0.05). The level of testosterone in the model group was reduced remarkably after Sitagliptin treatment (P < 0.001). The protein expression levels of DPP4, CTGF and TGF‐β1 in the ovarian stroma were lower in the treatment group than in the model group (P < 0.01, P < 0.001, P < 0.05). The mRNA levels of DPP4, CTGF and TGF‐β1 in the model group also greatly declined after Sitagliptin treatment (P < 0.05, P < 0.001, P < 0.01). CONCLUSION: The DPP4 inhibitor Sitagliptin lowers fasting blood glucose, relieves the high androgen state of PCOS rats and delays the process of ovarian fibrosis, which may be related to reducing the levels of factors related to the TGF‐β1/Smad2/3 signaling pathway.